Molecular Identification of Entamoeba Histolytica In Amoebiasis Patients - Ali Hassan Al-Timimi (Journal of Global Pharma Technology, 2018)
Infection is the third-greatest parasitic disease responsible for death in the world. Amoebic infections result either in a harmless colonization of the intestine, or in an amoebiosis with invasion and damage of the intestine, liver, lung, and brain. These distinct manifestations are due to the existence of Entamoeba Histolytica alone or with Entamoeba Dispar as a complex of two different, but morphologically identical species. One that is a nonpathogenic commensal in the intestine of humans, E. Dispar, and the other that is capable of inducing cell and tissue damage. Due to genomic DNA differences between pathogenic and nonpathogenic of these protozoan infections, we used a polymerase chain reaction (PCR) method that diagnosed and differentiated the two conditions. DNA extraction protocol using non-fixed stool samples.about60 of 65 stool specimens from patients with amoebiosis was characterized. Among them, 45 (75%) were infected only with the nonpathogenic species, E. Dispar, while 15 (25 %) displayed a mixed infection with the pathogenic nonpathogenic species, E. Dispar and E. Histolytica. The PCR protocol showed a specificity of 1.00 and a sensitivity of 0.95. The molecular approach is therefore reliable and applicable in the identification of pathogenic E. Histolytica infection. Present results provided tha importance data for the Iraqi Health Care System and   addressed the emerging problems of amoebic infection in Iraqi.Keywords: Entamoebahistolytiac, Molecular characterization, E. dispar, Stool sample.